KAJIAN PEMANFAATAN PUPUK ORGANIK DAN ANORGANIK TERHADAP PERTUMBUHAN DAN HASIL SAYURAN KENTANG - Thamrin, Muh.; Nurhayu, A.; , Ruchjaniningsih; Nappu, M. B. (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2014)
Assessment on Utilization of Organic and An-organic Fertilizer to Support Growth and Yield of Potatoes. In addition to reduce the dependence on anorganic fertilizers, utilization of organic fertilizers effectively will also contribute to improve the balance of ecosystems and support environmental-friendly farming system. This assessment aimed to find out effects of utilizing cacao skin waste, rice straw, and organic household garbage as organic fertilizer and to determine the effective application on growth and yield of potato. The study was conducted from May to December 2009 (dry season) in the central of potato development area in uplands in Malino, Bulu Ballea, Pattapang Village, Tinggimoncong District, Gowa Region, South Sulawesi. The experiment was arranged by a Randomized Completed Block Design (RCBD) consisted of five treatment combinations between organic and anorganic fertilizers using participatory three farmers as replications. The treatments were as follows: (A) 6 t/ha cacao skin waste + 500 kg/ha NPK (15:15:15), (B) 6 t/ha rice straw waste + 500 kg/ha NPK (15:15:15), (C) 6 t/ha household garbage waste + 500 kg/ha NPK (15:15:15), (D) 6 t/ha organic mixed + 500 kg/ha NPK (15:15:15), (E) Anorganic fertilizer dosage 1.000 kg/ha NPK (15:15:15).  The results showed that application of organic fertilizers from cacao waste caused different responses to plant height growth. While the organic fertilizer from rice straw waste had the highest production component of wight tuber per plant, number of tuber per plant and yield. The net income and cost obtained by advantage measurement was between Rp17.844.567 to Rp32.774.883 per hectare. There was none treatment combination of organic fertilizer that could be developed because the ratio of increasing net income and cost or Value Cost Ratio (VCR) < 1. However, seen from social aspects point of view, it might reduce the impact of environmental pollution as well as support sustainable agriculture. Key words: potato, organic waste, organic fertilizer, growth Pemanfaatan pupuk organik yang efektif selain dapat menghemat penggunaan pupuk anorganik juga berdampak positif terhadap perbaikan keseimbangan ekosistem dan mendukung pertanian ramah lingkungan. Percobaan ini bertujuan mengkaji pemanfaatan limbah kulit kakao, sampah rumah tangga dan jerami padi dan pupuk NPK terhadap pertumbuhan dan hasil tanaman kentang. Pengkajian dilaksanakan di daerah sentra pengembangan kentang di dataran tinggi Malino, Dusun Bulu Ballea, Kelurahan Pattapang, Kecamatan Tinggimoncong, Kabupaten Gowa, Sulawesi Selatan. Kajian berlangsung dari bulan Mei sampai Desember 2009 (musim kemarau). Kajian menggunakan Rancangan Acak Kelompok (RAK) yang terdiri atas 5 kombinasi perlakuan antara pupuk organik dan pupuk NPK yang melibatkan 3 orang petani sebagai ulangan.  Perlakuan yang dikaji ialah sebagai berikut: (A)  6 t/ha limbah kulit kakao + 500 kg/ha NPK (15:15:15), (B) 6 t/ha limbah jerami padi + 500 kg/ha NPK (15:15:15), (C) 6 t/ha limbah organik sampah rumah tangga + 500 kg/ha NPK (15:15:15),  (D) 6 t/ha Campuran + 500 kg/ha NPK (15:15:15), (E) pupuk anorganik dosis 1.000 kg/ha) NPK (15:15:15). Hasil penelitian menunjukkan bahwa pemberian pupuk organik dari limbah kulit kakao memberikan pengaruh terhadap komponen pertumbuhan tinggi tanaman yang berbeda nyata. Sedangkan  perlakuan pupuk organik dari limbah jerami menghasilkan bobot umbi/tanaman yang tertinggi, jumlah umbi/tanaman dan hasil. Penggunaan pupuk organik dan anorganik tersebut menghasilkan keuntungan antara Rp17.844.567- Rp32.774.883/ha. Meskipun tidak satupun kombinasi perlakuan pupuk organik layak untuk dikembangkan karena rasio kenaikan penerimaan dan biaya (Value Cost Ratio=VCR) < 1, tetapi dari aspek sosial aplikasi pupuk organik dapat mengurangi dampak pencemaran lingkungan akibat penggunaan pupuk anorganik yang berlebihan. Kata kunci :  kentang, limbah organik, pupuk organik, pertumbuhan